THE PRAGMATICS OF POLITENESS IN CROSS-CULTURAL COMMUNICATION - Khujabekova , Ramzida; Kuvandikova , Dildora (Scientific practical conference, 2026)
This article provides an expanded pragmatic analysis of politeness in English workplace dialogues, focusing on cross-cultural communication. Using a sample dialogue between a manager and an employee, the study examines face-threatening acts, positive and negative politeness strategies, and the linguistic markers that convey respect, mitigate imposition, and maintain social harmony. It highlights the role of cultural norms, social hierarchy, and contextual factors in shaping the interpretation of polite language. The article emphasizes the importance of pragmatic competence for effective communication in professional and multicultural environments and demonstrates how understanding politeness strategies can prevent miscommunication and foster interpersonal and intercultural understanding.